Pengaruh Modal Fisik dan Sumber Daya Manusia terhadap Indeks Inklusif di Indonesia - Reza Rizki Ramadhan; Yaya Setiadi (Jurnal Ekonomi Pembangunan, 2019)
Economic growth figures are one indicator to assess economic success. During the period of 2011-2017, Indonesia's economic growth rate was quite good, with at an average of 5,4 percent per year. However, these conditions have not been matched by a significant reduction in the level of poverty and inequality, and the level of employment has not been optimized. This indicates that the growth that has occurred has not been inclusive. This study to find out how the level of inclusive growth in Indonesia, measured by the inclusiveness index and the factors of development of physical capital and human resources that influence. The method of this study use panel data regression approach. The findings show that in the period 2011-2017, the level of inclusiveness index value in Indonesia is in the middle category. The variable of physical capital development in the form of government capital expenditure is statistically significant influencing the inclusiveness index in Indonesia, while the value of private capital investment has no significant effect. Human resource development variables, in the form of LFPR, RLS, and health complaints were statistically significant for the inclusiveness index in Indonesia, while government spending on education and health not significantly affected the inclusiveness index in Indonesia.